Prenatal myelomeningocele repair: Do bladders better?. Issue 6 (15th November 2016) - Horst, Maya; Mazzone, Luca; Schraner, Thomas; Bodmer, Christine; Möhrlen, Ueli; Meuli, Martin; Gobet, Rita
Abstract : Aims: Prenatal myelomeningocele (MMC) repair has been proven to significantly reduce the need for hydrocephalus shunting and improve lower‐extremity motor outcomes. The aim of this study was to evaluate the effect of prenatal MMC repair on the urological outcome. Methods: All patients who underwent fetal MMC repair at our institution are followed prospectively. Assessments include medical history, renal and bladder ultrasound, voiding cystourethrogram and urodynamic study, need for clean intermittent catheterization (CIC) and anticholinergics, and the occurrence of urinary tract infections (UTI). Results: Of the 30 patients who underwent prenatal MMC closure from December 2010 to December 2015, eight patients with a postnatal follow‐up of at least 2 years were included in this study and compared with eight patients after postnatal MMC repair. The level of the bony spinal defect was similar in both groups. Urological evaluation at 2 years revealed normal bladder function in 50% after prenatal repair. Neurogenic bladder dysfunction requiring CIC and anticholinergic therapy was seen in 50% in the prenatal and in 100% in the postnatal group. Significant bladder wall thickening was found in 37.5% and 87.5%, respectively. Febrile UTIs occurred in 37.5% in the prenatal and 62.5% in the postnatal group during the observation period. Conclusions: Our data suggest a positive effect of prenatal MMC closure on lower urinary tract function. The long‐term significance of these results remains unclear. Therefore, continued close monitoring of renal and bladder function are mandatory.